FAKTOR-FAKTOR NON KEUANGAN YANG MEMPENGARUHI OPINI AUDIT GOING CONCERN (Studi pada Perusahaan Sektor Jasa yang Tercatat di Bursa Efek Indonesia Tahun 2014-2017) - Rosiana Fitri; Anisma Yuneita; Putra Agri Adhitya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research aiming for analyze about effects of audit delay, debt default, audittenure, prior opinion, auditor switching, auditor's reputation, and disclosure on goingconcern audit opinion. Sample on this research is 100 financial reports from servicecompanies listed in Indonesia Stock Exchange period years 2014-2017. Sample takenusing purposive sampling method. Testing hypothesis processed with logistic regressionon Statistical Product and Service Solution (SPSS) version 23. The results indicate that:(1) audit delay is not affect going concern audit opinion with significance value 0,957 (2)debt default is significantly affect going concern audit opinion with significance value0,003 (3) audit tenure is not affect going concern audit opinion with significance value0,656 (4) prior opinions is significantly affect going concern audit opinion withsignificance value 0,000 (5) auditor switching significantly affect going concern auditopinion with significance value 0,038 (6) auditor’s reputation is not affect going concernaudit opinion with significance value 0,857 and (7) disclosure is not affect going concernaudit opinion with significance value 0.567.Keywords : going concern, audit delay, debt default, audit tenure, prior opinion,switching auditors, auditor’s reputation, and disclosure